PERLINDUNGAN HUKUM TERHADAP PEKERJA MIGRAN INDONESIA YANG MENGALAMI KEKERASAN DI LUAR NEGERI - Febrianti, Nadya Zerlinda; Afifah, Wiwik (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Migrant workers are one way to find income that is needed in everyday life. After the COVID-19 pandemic subsided, the interest in migrant workers increased again, due to the fact that their departure had been restricted before. With the large number of interested migrant workers, there are also increasing number of complaints of problems being overwritten by Indonesian Migrant Workers. The purpose of this research is to know and understand that the Indonesian government can have the authority to provide legal protection for Indonesian migrant workers who experience violence abroad. In this research, the journal uses normative methods and approaches to statutory regulations, as well as international conventions governing the Protection of the Rights of Migrant Workers and Family Members. The results of this study indicate that the protection provided by the government for migrant workers who experience violence can be carried out during pre-placement, placement, and post-placement, as well as the government's handling of migrant workers that must be carried out on Indonesian Migrant Workers both procedurally and non-procedurally. because the state has an obligation to fulfill the legal protection rights of every citizen